Mishandling of Testicular Swelling resulting in huge Scrotal Mass: drkashifbangash@hotmail.com - Bangash, Kashif; Naveed, Hania; Alam, Asaf; Anwar, Khursheed (International Journal of Pathology, 2018)
Abstract: Local spread of testicular tumor to the scrotum is very rare because of the investing tunica albuginea ofthe testis. The tunica once breached may lead to infiltration of the tumor cells in the scrotum. We present a case of a34 year old man who had a yolk sac carcinoma of the right testis for which orchiectomy was performed. He later onpresented with a huge fungating mass of the scrotum after 2 yrs. The mass got infected and he developed septicemia.